Multiphase fluidization in large-scale slurry jet loop bubble columns for methanol and or dimethyl ether production - Bakopoulos, A. (Chemical engineering science, 2006)
A solution methodology is proposed for the process development and process engineering of a continuously operated jet loop bubble column including integrated external or internal steam generation for, e.g., a high-efficiency large-scale medium pressure methanol and or dimethyl ether production, or other gas to liquid Fischer–Tropsch applications. A jet loop bubble column is defined in the present process development to study the combined integration of a jet-eductor draft tube system with an upper bubble column. The major advantages resulting from the integrated jet-eductor draft tube system in large-scale bubble columns are the guidance and good mixing efficiency of the multiphase flow up to the upper part of the bubble column. Reducing the bubble column operating liquid level at about 2.5–3.0 times of the column diameter above the upper end of the draft tube results in a classical jet-eductor draft tube reactor suitable for small and or medium-scale industrial applications. Methanol synthesis is usually executed catalytically in multistage packed beds at higher pressure, e.g. 26 MPa, and about 350– 400 ∘ C , resulting in a higher plant installation and operating cost. The successful scale-up of a slurry jet loop bubble column can achieve a higher catalytic selectivity at a lower pressure ( ∼ 5 MPa ) and temperature ( ∼ 250 ∘ C ) , and therefore reduce the overall plant investment and production cost [ Toseland, 1999. Three phase flows under extreme conditions of pressure and temperature, Part II: industrial applications, Air products and Chemicals, Inc. Presented at the A.I.Ch.E. Annual Meeting, Dallas, TX; Fan, 1999. Three phase flows under extreme conditions of pressure and temperature, Part I: fundmental characteristics, Department of Chemical Engineering, The Ohio State University. Presented at the A.I.Ch.E. Annuxal Meeting, Dallas, TX]. In addition, the separate slurry production of dimethyl ether, or even coproduction with methanol, can be a more cost-effective process than the classical methanol dehydration process. The new Modified Slurry Process © for large-scale methanol and or dimethyl ether production is presented including internal or external heat exchanger location for steam production. A process concept is developed of a Large Scale Slurry Jet Loop Bubble Column © with external separator, auxiliary internal heat exchanger equipment and high-efficiency gas–liquid slurry jet-eductor mixing system including draft tubes and an upper bubble column. In addition, as comparison a simplified concept is discussed for a small-to-medium-scale slurry jet loop reactor including external steam production and bottom nozzle jet-eductor installation without the presence of an upper bubble column. The basic geometrical parameters of the proposed slurry jet loop bubble column and jet loop reactor are discussed. The influence of the selected geometrical parameters on the gas holdup, interfacial area and mixing is analyzed. Information about catalyst type and particle size distribution is also presented. The definition of optimal operating conditions related to the influence of the fluid dynamics and mixing on mass transfer efficiency and also information for the minimum required power input per unit volume for startup or stable reactor operation are discussed. A simplified estimation method is presented for the expected axial temperature difference across the overall length of the jet bubble column, and also the required heat transfer area of a new construction-type internal compact heat exchanger for efficient reactor cooling and operation. Scale-up is possible for large diameter jet loop bubble columns, typically up to 5 m diameter and 60 m height, including continuous three-phase slurry operation at higher power input and interfacial area, for more efficient synthesis gas absorption and reaction than in classical slurry bubble columns. Integration of suitable designed sieve trays can further guarantee an efficient operation of the lower jet loop draft tube system at higher column diameters and also achieve an efficient reactor operation in the upper bubble column section.